Pengembangan Sistem Informasi Terintegrasi untuk Mendukung Pendaftaran dan Pemasaran UMKM (SITEKUM) di Kabupaten Bekasi - Aldi Friyatna Dira; Herman Susilo; Israfil Munawarah; Kurniawan Prambudi Utomo (Prima Abdika: Jurnal Pengabdian Masyarakat, 2025)
This community service program aims to socialize and develop SITEKUM (Integrated MSME Information System) as a digital platform to support the registration, data management, and marketing processes of MSME products in Kertarahayu Village, Setu District, Bekasi Regency. The village has considerable economic potential, particularly in MSMEs engaged in processed food products such as salak candy, cassava chips, and other traditional foods. However, MSME owners still face obstacles related to business legality, record-keeping, and access to technology-based promotion. The method used in this community service activity is Participatory Action Research (PAR), which emphasizes active collaboration between the community service team, MSME owners, and village officials. Data collection techniques include interviews, focus group discussions (FGDs), training sessions, and direct trials of the SITEKUM system. This approach was chosen to ensure that the system developed truly aligns with real needs in the field. The results show that SITEKUM can improve the efficiency of MSME data management, accelerate the registration process, and expand product marketing reach through online platforms. In addition, the active involvement of residents fosters a sense of ownership of the system and enhances the long-term sustainability of SITEKUM’s use.